Impact of obesity and allergic rhinitis on childhood asthma - E., Adarsh; K. V., Rajanish; P., Varun Prasannaa (International Journal of Contemporary Pediatrics, 2022)
Background: Bronchial asthma has varied presentations in children and its global prevalence is increasing in children. Asthma is associated with various risk factors and comorbidities. The objective of the study was to assess the severity, level of control of asthma in children without comorbidities, with obesity and allergic rhinitis. Methods: An observational study was conducted in 150 children aged 5-15 years diagnosed to have asthma as per GINA (Global initiative for asthma) guidelines 2019, who are being followed up in the department of pediatrics in asthma clinic in RRMCH. Parents were interviewed and the following data collected like demography, allergy history, treatment history, comorbidities, family history of atopy. Detailed clinical examination was performed including anthropometry-weight, height and BMI recording. Pulmonary function tests was done in all children. Results: Out of 110 children without comorbidities, 108 (98.2%) had well controlled, 2 (1.8%) had partly controlled, 0 had uncontrolled. Out of 19 children with obesity, 5 (26.3%) had well controlled, 9 (47.4%) had partly controlled, 5 (26.3%) had uncontrolled. Out of 15 children with allergic rhinitis, 6 (40%) had well controlled, 8 (53.3%) had partly controlled, 1 (6.7%) had uncontrolled. With a p value of 0.001, it is statistically significant. Conclusions: Our study shows severity of asthma increases in children having comorbidities like obesity and allergic rhinitis when compared with children without comorbidities with a significant association. Our study also shows that children having comorbidities like obesity and allergic rhinitis have poor level of asthma control when compared with children without comorbidities with a significant association.